Pragma Stylistic Features as an Interpretative Tool: An Analysis of Dawn Newspaper Headlines - Sundas Mehreen (University of Chitral Journal of Linguistics and Literature, 2021)
The combined studies of pragmatics and stylistics are less explored and often approached as pragma stylistics and pragmatics of style. The burgeoning field of interdisciplinary studies is well documented (Edwards, 1996, Klein 1990, 1996) and is the need of the day in this information age in order to get a clear understanding of the intricacies of language use in media texts. The fruitful link between pragmatics and stylistics can be exploited for an in-depth study of language use in media. However, the current study examines the representation of Pakistani English Newspaper headlines in terms of interpretation by adapting the Pragmatic Stylistic framework propounded by Black (2006). The sample for the study consists of 28 front-page headlines from The Daily Dawn, a top-rated and the oldest English newspaper in Pakistan. The data inquiry is undertaken with the analytical paradigm of descriptive qualitative interpretational analysis. The analysis provides evidence that pragmatic stylistics features govern the interpretation of the headlines from the writer/editor’s perspective. The variational use of Pragmatic Stylistic features in headlines cater to the variation of news events. The study concludes that being a governing factor in interpretation, Pragmatic Stylistic features are crucial to be understood by the writers.